Pemanfaatan Eceng Gondok (Eichhornia Crassipes) dalam Meningkatkan Kesuburan Tanah - Indah Cahyani Zega; Yanris Trisyana Mendrofa; Ernidar Mendrofa; Ayler Beniah Ndraha (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Using organic fertilizer can increase soil fertility, which is crucial for plant growth. Another organic material source that may be utilized as fertilizer is water hyacinth (Eichhornia crassipes). The chemical makeup of water hyacinth was examined in this study, and the results indicated that its organic matter content was 78.47%, its organic carbon content was 21.23%, its total nitrogen content was 0.28%, its total phosphorus content was 0.0011%, and its total potassium content was 0.016%. It has been demonstrated that applying water hyacinth-based liquid organic fertilizer to corn (Zea mays) plants actually affects crop output. Utilizing water hyacinth not only improves soil fertility but also lessens pollutants in the environment caused by overgrowth in waterways. Water hyacinth can therefore be utilized as a sustainable and eco-friendly organic fertilizer option.